Solus Jesus: a theology of resistance - Swan, Emily (Read the Spirit Books, 2018)
If you read one book this year about the future of Christianity, then choose this book. Five hundred years ago the Protestant Reformation claimed the Bible as the authoritative guide for Christian living ("Sola Scriptura!" Only Scripture!). In this groundbreaking work, Emily Swan and Ken Wilson claim the authority of the church is shifting back to where it should be: in Jesus (Solus Jesus!). As co-founders of Blue Ocean Faith, Swan and Wilson are pioneering what it means to be post-evangelical--post-Protestant, even--in a time when such re-imagining is desperately needed. Solus Jesus not only grapples with the authority question in Christianity, but also provides a massive re-think of traditional atonement theories. Leaning on the work of René Girard, they conclude that the life, death, and resurrection of Jesus together reveal a completely good, non-violent God who is on the side of the oppressed and scapegoated of this world. As a work of queer theology, the book is intersectional in its understanding of justice, and invites readers to reconsider our understanding of what it means to follow Jesus. This book is timely, to say the least. For Christians looking for guidance on how to address distressing issues of injustice; for help understanding how they can faithfully follow Jesus and love their neighbors as themselves; and for practices for how to experience the living Jesus and his Spirit of love--Solus Jesus is the book for you